At the boundaries: school networks in divided societies. Issue 2 (4th May 2020) - Robinson, Gareth; Gallagher, Tony; Duffy, Gavin; McAneney, Helen
Abstract : Purpose: This paper aims to demonstrate the transformative potential of school networks in divided societies, where separate schools often mirror wider ethnic divisions. It describes Shared Education in Northern Ireland, where networks are being utilised to change how Catholic and Protestant schools engage with one another. The concept of boundary crossing is used to frame how staff members build relationships and bridge distinct knowledge communities shaped by socio-cultural practices and identities. Design/Methodology/Approach: A mixed-methods design was employed. Evidence is presented based on a social network analysis of teacher interactions within a Shared Education partnership of five primary schools in Northern Ireland. Findings: The findings suggest that school networking can overcome systemic separation in divided societies and provide the infrastructure necessary to establish an alternative model for collegial engagement. The structural characteristics of the observed school network are discussed, including comments on its sustainability, the role of boundary-crossing relationships, the professional value for those involved and its transformative potential for society. Originality/value: This paper provides a unique perspective on the application and utility of school networks for supporting the development of professional communities in challenging circumstances. It also presents valuable social network data on the structure and management of school networks.